Effects of Choline on Meat Quality and Intramuscular Fat in Intrauterine Growth Retardation Pigs - Li, Bo (PLoS One, 2015)
The aim of this study was to investigate the effects of choline supplementation on intramuscular fat (IMF) and lipid oxidation in IUGR pigs. Twelve normal body weight (NBW) and twelve intrauterine growth retardation (IUGR) newborn piglets were collected and distributed into 4 treatments (Normal: N, Normal+Choline: N+C, IUGR: I, and IUGR+Choline: I+C) with 6 piglets in each treatment. At 23 d of age, NBW and IUGR pigs were fed basal or choline supplemented diets. The results showed that the IUGR pigs had significantly lower (P<0.05) BW as compared with the NBW pigs at 23 d, 73 d, and 120 d of age, however, there was a slight decreased (P>0.05) in BW of IUGR pigs than the NBW pigs at 200 d. Compared with the NBW pigs, pH of meat longissimus dorsi muscle was significantly lower (P<0.05), and the meat color was improved in IUGR pigs. The malondialdehyde (MDA) levels were significantly decreased (P<0.05), while triglyceride (TG) and IMF contents were significantly higher (P<0.05) in the IUGR pigs than the NBW pigs. IUGR up-regulated the mRNA gene expression of fatty acid synthetase (FAS) and acetyl-CoA carboxylase (ACC). Dietary choline significantly increased (P<0.05) the BW at 120d of age, however, significantly decreased (P<0.05) the TG and IMF contents in both IUGR and NBW pigs. FAS and sterol regulatory element-binding proteins 1 (SREBP1) mRNA gene expressions were increased (P<0.05) while the muscle-carnitine palmityl transferase (M-CPT) and peroxisome proliferators-activated receptorγ (PPARγ) mRNA (P<0.05) gene expressions were decreased in the muscles of the IUGR pigs by choline supplementation. Furthermore, choline supplementation significantly increased (P<0.05) the MDA content as well as the O(2)•¯ scavenging activity in meat of IUGR pigs. The results suggested that IUGR pigs showed a permanent stunting effect on the growth performance, increased fat deposition and oxidative stress in muscles. However, dietary supplementation of choline improved the fat deposition via enhancing the lipogenesis and reducing the lipolysis.